The New Emergent Multimedia Content And Digital Rights Management - Carvalho, Jeferson de (The Turkish Online Journal of Design Art and Communication, 2012)
Culture in the digital environment, after a drastic reduction in the cost of storage and editing, allowed remixing and faster sharing than in the analog age. The result of this new content is no longer published or presented through traditional forms known in the analog era. The old gatekeepers are no longer gatekeepers. Thus, copyright, once valid, conflicts with the dynamics of the digital culture. Digital Rights Management, used by a company as a tool, is an option to control and to guarantee economic interests. How can it become sustainable in order to create, to consume, to publish and to share multimedia content in this landscape?
Keywords: Technology; Communication; Multimedia; Social Network; Teknoloji; İletişim; Multimedya; Sosyal Ağ